2006
DOI: 10.2353/ajpath.2006.051231
|View full text |Cite
|
Sign up to set email alerts
|

Adoptively Transferred Allergen-Specific T Cells Cause Maternal Transmission of Asthma Risk

Abstract: In addition to genetics and environment, maternal asthma is an identified risk factor for developing the disease during childhood. The mechanisms of this maternal effect remain poorly understood. We tested the role of allergen-specific T cells in the maternal transmission of asthma risk by modifying a model where offspring of asthmatic mothers are more prone to develop asthma after an intentionally suboptimal asthma induction. Normal BALB/c females were injected with allergen-specific T cells from ovalbumin-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…A BALB/c model developed by L. Kobzik and colleagues (66, 68, 69) clearly reveals transmission of increased risk for development of allergic airway disease to offspring from mothers with Th2-biased OVAspecific immunity. In addition, suboptimal immunization of progeny facilitated their determination that both pre-and/or postnatal periods of exposure to allergic mothers are capable to enhance risk for development of asthma (66,68,69). In our study, C57BL/6 progeny from mothers with Th2-type immunity to OVA demonstrated no increase in susceptibility or severity of allergic airway disease when compared with progeny of naive mothers.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A BALB/c model developed by L. Kobzik and colleagues (66, 68, 69) clearly reveals transmission of increased risk for development of allergic airway disease to offspring from mothers with Th2-biased OVAspecific immunity. In addition, suboptimal immunization of progeny facilitated their determination that both pre-and/or postnatal periods of exposure to allergic mothers are capable to enhance risk for development of asthma (66,68,69). In our study, C57BL/6 progeny from mothers with Th2-type immunity to OVA demonstrated no increase in susceptibility or severity of allergic airway disease when compared with progeny of naive mothers.…”
Section: Discussionmentioning
confidence: 60%
“…The resultant data span the complete range from increased risk to increased protection. In addition, some transmitted maternal effects on susceptibility or severity of disease in offspring are Ag specific (61)(62)(63)(64), whereas others are independent of Ag (61,(65)(66)(67)(68)(69). The explanation for the great diversity in disease outcome depends on the model of maternal transfer studied and is likely determined by the contribution of unique immunological mechanisms expressed in the context of specific genetic, developmental, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol allows the distinction between inbred mice that are differentially susceptible to asthma, in an allergen nonspecific manner (18). This model has facilitated studies on the impact of maternal asthma on exposure to CpGs (20), breastfeeding (21), and allergen-specific T cell function during pregnancy (19). We found this model also suitable to study the role of early T cell subpopulations in the neonatal susceptibility to asthma.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, the interrelation between IL-4 and Treg function is thought to be a key event in the modulation of disease in asthmatic patients (64). Moreover, we have recently reported the existence of a cytokine imbalance, including a prominent role for IL-4 overproduction, during the pregnancy of asthmatic mother mice (18,19). Our present finding that, despite phenotypically normal Treg, spleen cellularity is increased in naive asthma-prone offspring further supports the concept that exaggerated Th2 cytokine production during pregnancy may weaken and/or deregulate neonatal T cell/Treg interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies show role of T-lymphocytes in maternal asthma transmission: adoptive transfer of allergenspecific T-lymphocytes to normal (non-asthmatic) females can cause increased susceptibility to asthma is offspring. Hubeau et al (2006) adoptively transferred allergen-specific T-lymphocytes from ovalbuminspecific T-cell receptor transgenic DO11.10 donors prior to mating. Following intraperitoneal injection of the DO11.10 T-lymphocytes and mating, the females showed no signs of an asthma phenotype, however their offspring had increased susceptibility to asthma when subject to the "suboptimal protocol" (Hubeau et al, 2006).…”
Section: Allergen Modelsmentioning
confidence: 99%